Neurosonology: a means of evaluating normal aging versus dementia. (October 2008) - Demarin, Vida; Baššic Kes, Vanja; Morovic, Sandra; Zavoreo, Iris
The aging of the population and higher life expectancy have led to an increase in the incidence of cognitive changes and dementia. It is important to differentiate between cognitive changes associated with normal aging and those associated with dementia. Dementia is a syndrome caused by a heterogeneous group of disorders, the most common being Alzheimer''s disease and vascular dementia. While cardiovascular risk factors, such as diabetes mellitus, hypertension, hypercholesterolemia, atrial fibrillation and smoking, are particularly relevant in the development of vascular dementia, they may also play a role in Alzheimer''s disease. The control of these risk factors at an early stage may help to delay the onset and reduce the severity of vasculopathy. Cognitive changes and vasculopathy are correlated with decreased mean blood flow velocities in the main arteries of the brain. Intracranial hemodynamics of the aging brain can sucessfully be assessed by a number of methods, including transcranial Doppler sonography (TCD), functional TCD and TCD detection of cerebral emboli. Extracranial circulation can be assessed by means of color Doppler flow imaging.